Contextual Inquiry Model to Improve Students’ Science Process Skill on Microbiology Lesson - Hasruddin, Hasruddin; Harahap, Fauziyah; Mahmud, Mahmud (Universitas Negeri Malang, 2018)
This study aims to develop the design of contextual inquiry learning model to improve students’ science process skills in microbiology lectures. The design of learning model developed in the form of contextual inquiry learning model. This Research and Development covers three stages of research that are: Needs analysis, Development of contextual inquiry learning model, and Trial of learning design. The research instruments used to collect data consisted of validation sheets by material experts, designers, and linguists, and a description test to measure the skills of the science process. It used descriptive statistics for data analysis. A preliminary study conducted on 40 students attending microbiology lesson indicated the need for microbiology teaching design which applies active learning process based on contextual inquiry. The results of a limited trial of 34 experimental class students and 35 control class students found that the research hypothesis was accepted, which means that contextual inquiry learning model of microbiology enhances students’ process skills higher than conventional method. Penelitian ini bertujuan untuk mengembangkan desain model pembelajaran inkuiri kontekstual untuk meningkatkan keterampilan proses sains siswa dalam perkuliahan mikrobiologi. Desain model pembelajaran dikembangkan dalam bentuk model pembelajaran inkuiri kontekstual. Penelitian dan Pengembangan ini mencakup tiga tahap penelitian yaitu: Analisis kebutuhan, Pengembangan model pembelajaran inkuiri kontekstual, dan Ujicoba desain pembelajaran. Instrumen penelitian yang digunakan untuk mengumpulkan data terdiri dari kuesioner kepada ahli materi, ahli desain pembelajaran, dan ahli bahasa, serta tes objektif untuk mengukur keterampilan proses sains. Data dianalisis dengan menggunakan statistik deskriptif. Studi pendahuluan yang dilakukan pada 40 mahasiswa yang sedang mengikuti perkuliahan mikrobiologi menunjukkan perlunya desain pembelajaran mikrobiologi dengan menerapkan proses pembelajaran aktif berbasiskan inkuiri kontekstual. Hasil uji coba terbatas terhadap 34 siswa kelas eksperimen dan 35 siswa kelas kontrolditemukan bahwa hipotesis penelitian diterima, yang berarti bahwa model pembelajaran inkuiri kontekstual pada perkuliahan mikrobiologi dapat meningkatkan keterampilan proses mahasiswa lebih tinggi daripada model pembelajaran langsung.